Nutrient Values of Utilization of Crops Wastes as Alternative Pig Feeding Ingredient in The Coastal Agro-Ecological Area of Manokwari, West Papua - Freddy Pattiselanno; Desni T.R. Saragih; Marlyn N. Lekitoo; Deny Anjelus Iyai (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2021)
The purpose of this study was to determine the potential nutritional value of livestock feed ingredients from agricultural products and their waste (by-product / residues) that had been utilized by pig farmers in Manokwari. This research was conducted by a survey method of some agricultural commodity-based animal feed sources and their associated results at 10 sampling locations. Feeds are collected and analyzed according to the proximate analysis of feed ingredients at the Nutrition and Animal Feed laboratory, Bogor Agricultural University. Samples of farmers are chosen purposely on smallholder farmers who have been utilizing these feed sources. Data were analyzed descriptively. The results of the study found that feed was used by combining food waste originating from markets, restaurants, fried food sellers, fish auctions, garden products and kitchen wastes (swill-feed). Types of feed from various sources are mixed and cooked together before being given to pigs. Food waste is obtained free of charge, but there is a small portion that buys and a combination of both. Feeding is practiced 1-3 times a day. Nutrient content (g/100 g) in the form of water was 9.47, PK 25.10, fat 11.75 g, SK 7.96, GE 4308.90, ash 8.58, Ca 2.35 and P 0.94. The SNI standards have met the standard criteria to be prepared and given to pigs.